ANALISIS KOMPARATIF KINERJA KEUANGAN PT. EASTPARC HOTEL tbk TERHADAP PERUSAHAAN SEKTOR SEJENIS YANG TERDAFTAR DI BEI SEBELUM DAN SAAT PANDEMI COVID-19 PERIODE 2018-2020 - Astuti, Ayu (OBOR: Oikonomia Borneo, 2020)
The purpose of this study was to determine, analyze, and compare the financial performance of PT. Eastparc Hotel Tbk with similar sector companies (sample) before and during the 2018-2020 COVID-19 pandemic which were analyzed based on the liquidity ratio (current ratio and cash ratio), solvency ratio (total debt to equity ratio and total debt to total assets), activity ratio (total assets turnover), and profitability ratio (return on assets and net profit margin). This research method is descriptive qualitative by using financial ratio analysis tools to determine and analyze the value of liquidity (current ratio and cash ratio), solvency value (total debt to equity ratio and total debt to total assets), activity value (total assets turnover), and profitability values ​​(return on assets and net profit margin), which are then compared between the companies that the researcher chooses with other similar sector companies. From the analysis results, the researcher can conclude that the liquidity ratio (current ratio and cash ratio), solvency ratio (total debt to equity ratio and total debt to total assets), and activity ratio (total asset turnover) are below the industry average or more. lower than the industry average (sample), while the profitability ratios (return on assets and net profit margin) are above the industry average or higher than the industry average (sample).